Gut microbiome patterns correlate with higher postoperative complication rates after pancreatic surgery - Schmitt, Felix; Brenner, Thorsten; Uhle, Florian; Loesch, Svenja; Hackert, Thilo; Ulrich, Alexis; Dalpke, Alexander; Weigand, Markus A.; Boutin, Sébastien (BMC microbiology, 2019)
Postoperative complications are of great relevance in daily clinical practice, and the gut microbiome might play an important role by preventing pathogens from crossing the intestinal barrier. The two aims of this prospective clinical pilot study were: (1) to examine changes in the gut microbiome following pancreatic surgery, and (2) to correlate these changes with the postoperative course of the patient.
Gesehen am 31.05.2019